Conflict resolution styles as predictors of marital adjustment and marital satisfaction: an actor-partner interdependence model - Unal, Ozge; Akgün, Serap (Routledge Journals, Taylor & Francis Ltd, 2022)
The aim of the study was to examine the mediating role of marital adjustment on the relationship between conflict resolution styles and marital satisfaction in terms of actor and partner effects. It was hypothesized that the marital adjustment mediates the effect of conflict resolution styles on marital satisfaction. One hundred and fifty-five married couples participated in the study. Conflict Resolution Styles Inventory, Revised Dyadic Adjustment Scale, and Relationship Satisfaction Scale were used to collect the data. The hypotheses were tested using Actor Partner Interdependence Model (Kenny et al.,2006). According to the results, both wives' and husbands' positive problem-solving styles predicted their own marital satisfaction via marital adjustment. In addition, husbands' positive and negative problem-solving styles predicted both their own and their wives' marital satisfaction through marital adjustment.
Keywords: APIM; conflict resolution styles; gender roles; marital adjustment; marital satisfaction